Influence of Rainfall on Leptospira Infection and Disease in a Tropical Urban Setting, Brazil - Hacker, Kathryn P. (Emerg Infect Dis, 2020)
The incidence of hospitalized leptospirosis patients was positively associated with increased precipitation in Salvador, Brazil. However, Leptospira infection risk among a cohort of city residents was inversely associated with rainfall. These findings indicate that, although heavy rainfall may increase severe illness, Leptospira exposures can occur year-round.